Technical Progress, Unemployment and Wealth - M. V. Safronchuk (Vestnik MGIMO-Universiteta)
This text examines the dynamic of unemployment, prices and wages under the technical progress. It also describes the way in which big economic cycles change the main macroeconomic indicators, including saving-investment decisions. We present a version, that the long wave goes down our days and can change the expectations and psychological factors of economic behavior.